2012
DOI: 10.3892/or.2012.1738
|View full text |Cite
|
Sign up to set email alerts
|

The heat shock protein 90 inhibitor SNX-2112 inhibits B16 melanoma cell growth in vitro and in vivo

Abstract: Abstract. SNX-2112 is a selective heat shock protein 90 (Hsp90) inhibitor which can exert a potent anticancer activity. In this study, we investigated the effects of SNX-2112 on B16 melanoma cells in vitro and in vivo. The 3-(4,5-dimetrylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay and flow cytometric analysis demonstrated that SNX-2112 dosedependently inhibited the growth of B16 cells, and induced G0/ G1 cell cycle arrest and apoptosis. Western blotting revealed that SNX-2112 lead to the degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…SNX-2112 more potently inhibited melanoma cell proliferation than 17-AAG [133,134], and arrested cells in G0/G1 phase of cell cycle in a dose-dependent manner [133]. SNX-2112 induced a time-dependent degradation of HSP90 client proteins crucial for melanoma cell maintenance including AKT, IKKα, BRAF and glycogen synthase kinase 3 beta (GSK-3β) [133]. SNX-2112 also induced apoptosis in melanoma cells [132,134], which was associated with an activation of caspase-3, caspase-7 and caspase-8, and PARP cleavage.…”
Section: Non-resorcinol Pyrazole Inhibitorsmentioning
confidence: 94%
See 1 more Smart Citation
“…SNX-2112 more potently inhibited melanoma cell proliferation than 17-AAG [133,134], and arrested cells in G0/G1 phase of cell cycle in a dose-dependent manner [133]. SNX-2112 induced a time-dependent degradation of HSP90 client proteins crucial for melanoma cell maintenance including AKT, IKKα, BRAF and glycogen synthase kinase 3 beta (GSK-3β) [133]. SNX-2112 also induced apoptosis in melanoma cells [132,134], which was associated with an activation of caspase-3, caspase-7 and caspase-8, and PARP cleavage.…”
Section: Non-resorcinol Pyrazole Inhibitorsmentioning
confidence: 94%
“…SNX-2112 is an N-terminal domain binding HSP90 inhibitor containing the 2-aminobenzamide scaffold [132]. SNX-2112 more potently inhibited melanoma cell proliferation than 17-AAG [133,134], and arrested cells in G0/G1 phase of cell cycle in a dose-dependent manner [133]. SNX-2112 induced a time-dependent degradation of HSP90 client proteins crucial for melanoma cell maintenance including AKT, IKKα, BRAF and glycogen synthase kinase 3 beta (GSK-3β) [133].…”
Section: Non-resorcinol Pyrazole Inhibitorsmentioning
confidence: 99%
“…At the same time, they found that suppression of Hsp90 effectively targeted the functionality of thyroid CSCs, which prevented their migration and invasion (White et al, 2016). In our previous studies, the Hsp90 inhibitor SNX-2112 demonstrated antitumor activity by induction of apoptosis and cell cycle arrest of melanoma cells, and inhibiting tumor growth in vivo (Liu et al, 2012a;Liu et al, 2012b;Wang et al, 2014). In addition, it exerted its inhibitory effect on various cancer cells by binding to the N-terminal adenosine triphosphate binding site of Hsp90 (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…We have previously proven that SNX-2112 was a novel, highly efficient, and highly selective small molecule inhibitor of Hsp90 that could competitively integrate with the N-terminal ATP-binding site of Hsp90 and exhibit anticancer activity in cancer cells, including breast cancer [34], multiple myeloma [35], melanoma [36, 37], chronic myeloid leukemia [38], esophageal cancer [39], and head and neck squamous cell carcinomas [40]. Especially in human hepatocellular carcinoma cells, SNX-2112 could induce apoptosis, elevating the role of ER stress [41].…”
Section: Introductionmentioning
confidence: 99%